Nonlinear optical and quantum chemical studies of Palladium benzimidazole Schiff base complex. (15th November 2022) - Manjunatha, K.B.; Supriya, S.; Shakeel Nawaz, S.; Ranjan, Prabhat; Chakraborty, Tanmoy; Poornesh, P.; Dileep, R.
Abstract: This article presents the linear and nonlinear optics and density functional theory studies of a Palladium complex with a benzimidazole-based Schiff base. Linear absorption of the complex has been studied using a UV–Vis absorption spectrometer. Optical nonlinearity and thereby the optical limiting performance of the complex has been deliberated experimentally using a Z-scan method with a continuum wave laser of wavelength 532 nm. The NLO investigation of the complex demonstrated significant nonlinear absorption (βeff = 4.64–27.23 × 10 −2 cm/W) with an imaginary part of nonlinear optical susceptibility of the third-order (Imχ (3) = 1.28–7.49 × 10 −5 esu) and nonlinear refraction (n2 = 5.46–12.3 × 10 −7 cm 2 /W) with real part of nonlinear optical susceptibility of the third-order (Reχ (3) = 3.55–8.00 × 10 −5 esu). The large nonlinear absorption displayed superior optical power limiting characteristics with a threshold and clapping level of 115 W/cm 2 and 35 W/cm 2 respectively. Theoretical studies are performed for Palladium benzimidazole Schiff base complex within Density Functional Theory (DFT) framework, using hybrid exchange-correlation B3LYP with basis set LANL2DZ. DFT-based descriptors are computed viz. energy gap between HOMO-LUMO, electronegativity, electrophilicity index, molecular hardness, and softness. Result reveals that the bond length between Pd–O is small as compared to Pd–Cl and Pd–N. Graphical abstract: Image 1 Highlights: An easily synthesizable Palladium complex with benzimidazole based Schiff base ligand. Simple, but highly effective chemistry of the molecule in a non-symmetric environment. High optical nonlinearity in the complex is due to excellent charge communication between various groups.